Penerapan Digital Marketing Terhadap Strategi Pemasaran Pada UMKM Skala Kecil Di Tigaraksa - Faisal R, M Rafly (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2024)
Abstract: Implementation of Digital Marketing for micro, small, and medium enterprises (MSMEs) to increase business income and get convenience in identifying consumer needs and desires, There are still many business actors who have not implemented marketing strategies with digital marketing. Including small-scale food and beverage MSMEs in the Tigaraksa area. Therefore, the implementation of this digital marketing is intended to help business actors achieve maximum results in implementing marketing strategies, and increase branding of business actors to achieve a large scale that can be recognized by the wider community, from within and outside the area in Tigaraksa-Tangerang. The methods used are direct discussions and training for business actors in Tigaraksa with small-scale criteria. The results of the discussion and training can improve the quality of MSMEs in the knowledge of digital marketing strategies, which are applied to small-scale MSMEs to brand their businesses in order to achieve maximum profits and make their businesses large-scale.